Implementasi Problem Tree Analysis Dalam Pengambilan Keputusan Terkait Penutupan Gang Dolly Oleh Pemerintah Kota Surabaya - Abidah Nabilah; Salsabila Putri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The high rate of prostitution in the city of Surabaya has caused various problems in the city. Gang Dolly localization is the largest prostitution business in Southeast Asia that has violated morals and created an increase in crime rates, such as abuse, drug use, theft, and human trafficking, namely exploitation of women. So the Surabaya City Government made a decision to close the Gang Dolly localization. This is in line with the policy of Regional Regulation No. 7/1999 on the Prohibition of Using Buildings/Places for Immoral Acts and Solicitation to Perform Immoral Acts. The purpose of this research is to find the root cause of the existence of Gang Dolly. The method used in the preparation of this article is a systematic literature review using the Problem Tree Analysis technique. The causes of the closure of dolly alley were caused by several things such as the high economic pressure experienced by prostitutes, low interest in pursuing higher education, lack of firm policy implementation, the existence of historical traces that were used as reasons for the establishment of dolly alley, and social influences that had an impact on the mindset of prostitutes. These causes have an impact on prostitutes and the community such as the high rate of spread of HIV and AIDS, the high rate of crime and exploitation of women, the disruption of biological and psychological growth in early childhood, the emergence of a negative stigma towards prostitutes that creates high social pressure, and the poor image of the city of Surabaya.